2014
DOI: 10.1016/j.jad.2014.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence that severe scores in the aggression/anxiety-depression/attention subscales of child behavior checklist (severe dysregulation profile) can screen for bipolar disorder symptomatology: a conditional probability analysis

Abstract: Background Previous work shows that children with high scores (2 SD, combined score ≥ 210) on the Attention Problems, Aggressive Behavior, and Anxious-Depressed (A-A-A) subscales of the Child Behavior Checklist (CBCL) are more likely than other children to meet criteria for bipolar (BP)-I disorder. However, the utility of this profile as a screening tool has remained unclear. Methods We compared 140 patients with pediatric BP-I disorder, 83 with attention deficit hyperactivity disorder (ADHD), and 114 contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
4
23
0
Order By: Relevance
“…While different measures have been used to operationalize emotional dysregulation, multiple studies reported that emotional lability and emotional reactivity were significant predictors of manic switches in pediatric MDD. These findings are consistent with studies that reported that severe forms of emotional dysregulation defined through marked elevations in specific scales of the CBCL predicted both lifetime and current diagnosis of bipolar disorder in youth with ADHD (Faraone et al, 2005;Uchida et al, 2014). Biederman et al (2009bBiederman et al ( , 2012 also found that a positive CBCL severe emotional dysregulation profile predicted a subsequent diagnosis of bipolar disorder, impaired psychosocial functioning and higher risk of psychiatric hospitalization in youth with ADHD followed prospectively into young adult years.…”
Section: Discussionsupporting
confidence: 89%
“…While different measures have been used to operationalize emotional dysregulation, multiple studies reported that emotional lability and emotional reactivity were significant predictors of manic switches in pediatric MDD. These findings are consistent with studies that reported that severe forms of emotional dysregulation defined through marked elevations in specific scales of the CBCL predicted both lifetime and current diagnosis of bipolar disorder in youth with ADHD (Faraone et al, 2005;Uchida et al, 2014). Biederman et al (2009bBiederman et al ( , 2012 also found that a positive CBCL severe emotional dysregulation profile predicted a subsequent diagnosis of bipolar disorder, impaired psychosocial functioning and higher risk of psychiatric hospitalization in youth with ADHD followed prospectively into young adult years.…”
Section: Discussionsupporting
confidence: 89%
“…For example, the CBCL Attention Problems scale differentiates youth with ADHD and anxiety from youth with anxiety without ADHD in a clinic for children with anxiety, 4 and combining several subscales of the CBCL can differentiate clinical youth with ADHD alone from clinical youth with bipolar I from a specialty clinic and other sources with or without ADHD. 5 Finally, the study is consistent with efforts in the UK to establish ROC criteria for diagnosing ADHD with the Strengths and Difficulties Questionnaire, a low-burden, broad-based instrument in the public domain. Its subscale Hyperactivity/Inattention generates DLRs that are able to differentiate clinical youth with and without ADHD.…”
supporting
confidence: 76%
“…A proxy for BD with an elevation of the anxious/depressed, aggressive behavior, and attention problems subscales (often referred to as CBCl-dysregulation profile) has been found to accurately differentiate BD from ADHD [39,40], but other studies found that this proxy was not specific to BD, even though subjects with BD were more likely than ADHD to have the CBCl-dysregulation profile [41,42] ( Table 1).…”
Section: Clinical Featuresmentioning
confidence: 99%